Global Warming and Climate Change - Effect and Strategies for its Mitigation - Bhardwaj, S. D.; Panwar, Pankaj (Indian Forester, 2003)
This article surveys predicted and projected rates of glohal warming and climate change due to emission of GHGs and their consequences especially effects on nature , society , glaciers and stream flow , agriculture and fauna. Effects on forests may result in shift of species , drop in productivity and growth , increased incidence of insects. To counter these problems , a worldwide strategy has to be taken up to mitigate or slow down these processes. In this strategy the international agencies can playa dominant role in fixing targets for reduction of emission. Geo-engineering can be put to use but the forests have the biggest opportunity as they absorb CO2 and function as carbon sinks. The introduction of carbon credits is advocated , as an incentive.